2020
DOI: 10.21037/cdt-20-510
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of influencing factors related to elevated serum troponin I level for COVID-19 patients in Yichang, China

Abstract: Background: Cardiac injury is a common condition among hospitalized coronavirus disease 2019 (COVID-19) patients, and is associated with a higher risk of mortality. However, the mechanism of myocardial injury in COVID-19 remains unclear. In this retrospective study, we compared the clinical characteristics of COVID-19 patients with different troponin I (TnI) levels during hospitalization to provide a clinical reference for the identification of those at high-risk. Methods: In total, 218 patients diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…The ndings on demographic and clinical/laboratory data of the two ICU cohorts con rmed previous studies that found that age and obesity may contribute to the severity of the disease, as assessed by the PaO2/FiO2 ratio, the APACHE II index, and length of ICU stay [24]. They also validate previous studies showing that a marker of heart injury such as troponin is associated with age and in ammation (IL-6) [25].…”
Section: Discussionsupporting
confidence: 84%
“…The ndings on demographic and clinical/laboratory data of the two ICU cohorts con rmed previous studies that found that age and obesity may contribute to the severity of the disease, as assessed by the PaO2/FiO2 ratio, the APACHE II index, and length of ICU stay [24]. They also validate previous studies showing that a marker of heart injury such as troponin is associated with age and in ammation (IL-6) [25].…”
Section: Discussionsupporting
confidence: 84%
“…One study showed that 41 (22%) of admitted patients had myocardial injury and the mortality was similar among those with myocardial injury regardless of whether they had or did not have COVID-19 infection [47]. The included studies also examined the relationship between troponin level and mortality or the prevalence of elevated cardiac enzymes among hospitalized COVID-19 patients [35,39,41,44,51,52,54,58,61,66].…”
Section: N Resultsmentioning
confidence: 99%
“…Therefore, increased Mb may be used as a determinant of adverse COVID-19 outcomes. Also, [50] Who observed that the percentages of patients COVID-19 and unvaccinated with elevated MYO concentration were greater in the group with raised TnI. The biomarker was specific to MYO for the acute assessment of myocardial infarction and coronary heart disease.…”
Section: Estimation Of Serum Myoglobin Concentrationsmentioning
confidence: 89%